Crisis Analysis and Prevention and Control of Financial Leverage Imbalance in Shareholder Equity Pledge Based on the DANP Model - Fang Fang (Discrete Dynamics in Nature and Society)
ResearchBackground. The process of economic globalization is accelerating, and the financial risks that listed companies need to face are more complicated. Research Purpose. In order to clarify the impact of shareholder equity pledge on financial leverage imbalance crisis, research on the analysis and prevention of financial leverage imbalance crisis of shareholder equity pledge based on the DANP model is carried out. Research Method and Process. The DANP financial leverage imbalance early warning model is introduced to analyze the impact of shareholder equity pledge on financial leverage imbalance crisis by combining the financial leverage effect and potential risks of shareholder equity pledge, optimize the financial leverage imbalance early warning evaluation index system, preprocess the early warning evaluation indicators, determine the constant weight of each evaluation index, and obtain the final financial leverage imbalance crisis early warning evaluation value based on the determined constant weight. Research Results. The DANP model can accurately analyze the financial leverage imbalance crisis in the case of shareholder equity pledges, clarify the company’s financial status in the case of shareholder equity pledges, propose to standardize equity pledge behavior, improve the company’s internal control system in response to the crisis of shareholder equity pledge financial leverage imbalances, and improve the three prevention and control measures of the independent director system to enhance the ability of enterprises to resist the crisis of financial leverage imbalance.